Impact of Corporate Governance on Firm Efficiency: A Study of Thai Banking Companies - Sharma, Keertiman; Ow-jariyapithak, Duangjai; Dasri, Piyada; Van Brecht, David; Sahakijpicharn, Danuch (International Journal of Multidisciplinary in Management and Tourism, 2021)
Corporate governance refers to the system by which organizations are directed and controlled. The need for and the relative importance of corporate governance arose in the 1980s due to poor corporate governance, which led to a loss in the value of firms, a downturn in economies, trust deficit in businesses, and corporate responsibility scandals. Good corporate governance will help in reassuring the stakeholders that an organization’s Board of directors (BOD) and top management are acting as worthy agents of their principal (the shareholders). Firm efficiency is the effective utilization of a firm’s resources to generate more revenues. The present paper addresses whether a positive relationship exists between corporate governance and firm efficiency in Thai Banking companies. It analyzes whether good corporate governance leads to better firm efficiency and helps users’ decision-making. For this purpose, the corporate governance scores (CG scores) of eleven (11) Thai banking companies (Public Companies Limited) have been compared and evaluated with their firm efficiency for each of the five years from 2015 to 2019. Data Envelopment Analysis (DEA) has been performed on essential financial items to determine firm efficiency. These financial items relate to the ones used in DuPont analysis. They have been obtained from the banks’ financial statements. The findings report the change in CG scores and DEA firm efficiency of Thai banking companies and the impact of corporate governance on the efficiency of these firms. There is a clear and positive relationship between corporate governance and firm efficiency for most Thai banking companies but not for all of them.